La-Hexaaluminate Catalyst Preparation and Its Performance for Methane Catalytic Combustion - 崔梅生 王良士 赵娜 龙志奇 李殿卿 陈霭璠 (Journal of rare earths, 2006)
The La-hexaaluminate catalysts with high performance ration method with the buffer solution of NH4HCO3 and NH4OH were synthesized by the modified controllable co-precipimixture as the precipitation agent. The physicochemical properties of catalysts were characterized by the means of BET, XRD, and TPR techniques. With methane catalytic combustion as the probe reaction, the catalytic performances were also tested on a fixed bed, continual flow system. The resuits show that it is a good method to obtain chemical homogeneous hexaaluminate materials by the buffer solution as the precipitation agent. The La-hexaaluminate can be formed at low temperatures ranging from 1050 to 1200 ℃. The cerium introduction plays a great role in the methane catalytic combustion on La-Mn hexaaluminate because of its high oxygen storage capacity property and the well synergic effect between Ce and Mn. However, the CeO2 appears in hexaaluminate through the XRD pattern, which reveals that Ce can not enter the crystal lattice position. Mn introduction improves the methane catalytic activity to a large extent due to its high redox property. When Mn atomic substitution amount for A1 is 2, the hexaaluminate shows the highest activity, and the catalyst possesses good H2 consumption and redox performance. Mn can easily occupy the hexaaluminate crystal position, which reveals that the Mn substitute La-hexaaluminate is a promising high temperature methane combustion catalyst with high activity and good stability.